2022
DOI: 10.1108/ijoes-06-2021-0117
|View full text |Cite
|
Sign up to set email alerts
|

Investigating boycotts and buycotts as antecedents towards attitude and intention to engage in ethical consumption

Abstract: Purpose This paper aims to investigate the attitude towards ethical consumption and intention to engage in ethical consumption behaviour by consumers within a developing economy, building on the ethically minded consumer behaviour (EMCB) framework. Design/methodology/approach A quantitative research approach was adopted in this research. A cross-sectional survey was further done in collecting data from 397 respondents through an online questionnaire. Collected data was analysed using the Statistical Package … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 92 publications
1
2
0
Order By: Relevance
“…Steenhaut and Van Kenhove (2006) also empirically validated that ethical beliefs influence an individual's intentions to engage in ethically questionable conduct. In the context of consumer ethics, similar findings were reported from other studies that CEBs largely influence consumers' subsequent ethical/unethical actions (Akintimehin et al, 2022;Chang and Lu, 2019;Zhao and Xu, 2013). Furthermore, Liu et al (2009) and Chang and Lu (2019) found that CEBs and ethical behaviour are positively related, such that consumers with a high level of ethical beliefs show less propensity to perpetrate questionable behaviour.…”
Section: Consumer Ethical Beliefs and Unethical Consumer Behavioursupporting
confidence: 83%
“…Steenhaut and Van Kenhove (2006) also empirically validated that ethical beliefs influence an individual's intentions to engage in ethically questionable conduct. In the context of consumer ethics, similar findings were reported from other studies that CEBs largely influence consumers' subsequent ethical/unethical actions (Akintimehin et al, 2022;Chang and Lu, 2019;Zhao and Xu, 2013). Furthermore, Liu et al (2009) and Chang and Lu (2019) found that CEBs and ethical behaviour are positively related, such that consumers with a high level of ethical beliefs show less propensity to perpetrate questionable behaviour.…”
Section: Consumer Ethical Beliefs and Unethical Consumer Behavioursupporting
confidence: 83%
“…Therefore, customers judge fashion goods, and the judgments shape their views about such goods. Consumers often have favorable opinions about sustainable fashion items (Akintimehin et al, 2022; Kong & Ko, 2017) and specifically towards upcycled fashion products that can be attributed to perceived uniqueness. Han et al (2017) and Paras and Curteza's (2018) research reinforce the notion that repurposed clothing is distinctive.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We only found a few variables raised as mediators and moderators, unlike predictive variables. In a study conducted by Duong (2022) and Akintimehin et al, (2022), we noted that intention and attitude towards green products have a significant role in mediating personality traits towards sustainable behavior. Then, consumer engagement with the environment is also proven to mediate sustainable behavior (Kadic-Maglajlic et al, 2019;Piligrimiene et al, 2020).…”
Section: Updating Dimensions and Related Driving Factors In Responsib...mentioning
confidence: 92%